1977
DOI: 10.1128/iai.16.1.258-262.1977
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of delayed hypersensitivity in mice to microbial antigens with dialyzable transfer factor

Abstract: Dialyzable Lawrence-type transfer factor was prepared from the spleen cells of CF1 mice inoculated with Coccidioides immitisand Candida albicans-killed vaccines and with live Mycobacterium tuberculosis vaccine (BCG). These preparations were shown to transfer antigen-specific cell-mediated immunity to naive mice, as measured by the delayed skin test and footpad-swelling methods. Reactivity could be demonstrated when the test antigens were given 24 h after the transfer factor, but not when they were given simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Very few previous studies have demonstrated transfer of DTH with TF in mice. Rifkind et al found that a TF-like substance prepared from spleen cells of CF1 mice was capable of transferring antigen-specific footpad responsiveness to recipient mice (19). They also confirmed Crowle's earlier work showing that footpad swelling is a valid indicator of DTH in mice (7,17).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Very few previous studies have demonstrated transfer of DTH with TF in mice. Rifkind et al found that a TF-like substance prepared from spleen cells of CF1 mice was capable of transferring antigen-specific footpad responsiveness to recipient mice (19). They also confirmed Crowle's earlier work showing that footpad swelling is a valid indicator of DTH in mice (7,17).…”
Section: Resultsmentioning
confidence: 59%
“…These studies establish that a TF-like substance does exist in murine spleen cells, and that sensitivity to at least one microbial antigen can be transferred with this moiety. Biochemical characterization of this substance and its relation both to the material obtained by Rifkind et al (19) in a different inbred mouse strain and to human TF will be of interest. Further studies with other antigens will also be important.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As previously noted, other investigators have demonstrated the specificity of various TF preparations in animal models (9,11,18,21,25). In this study we did not attempt to challenge the mice with other strains of Salmonella after TF administration to determine whether cross-protection existed.…”
Section: Discussionmentioning
confidence: 93%
“…Rifkind et al (21) have successfully transferred DH in mice to several fungal and bacterial antigens with murine-derived TF. The murine TF was found to be sensitive to the enzymes pronase and dimerized RNase A, but resistant to degradation by trypsin and monomeric RNase (20).…”
mentioning
confidence: 99%